Sexual profile and frequency of genital infections in teenagers treated in the university clinic - Souza, Luana R.; Filgueiras, Andréa S.; Silva, Artur B. T.; Souza, Roberta R.; Reis, Helena Lucia B.; Godefroy, Phillipe; VHerdy, Gesmar; Paixão, Louise A.R.; Andrade, Marilda; Calderaro, Martinha; et al. (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Introduction: nowadays, young people are in vulnerable situation for genital infections, due to high rates of sexual activity with different partners and failures in the use of condoms. Objectives: describe the sexual profile and frequency of genital infections diagnosed in adolescents seen in a DST Clinic of Federal Fluminense University (UFF) in the years 2005 and 2006. Methods: a cross-sectional study was conducted, descriptive, observational and quantitative through records analysis of adolescents between 12 and 19 years of age attended in DST/UFF Sector from January to December of the years 2005 and 2006. The data was processed through descriptive analysis by percentage. Results: the share of teenagers who attended the service was equal for both sexes, but the majority over 16 years of age, with fixed sexual partner only in 57.2% of cases in 2005 and 57.63% for the year 2006, in which the majority did not use condoms and had no history of the DST in both years of study. Of these 46.9% (2005) and 38.98% (2006) had incomplete primary school and 50.3% (2005) and 55.93% (2006) were students. The sexual initiation occurred around 13 years of age and genital infection by the human papilloma virus (HPV) was described as the most frequent in this group. Conclusion: teenagers are a vulnerable group in relation to sexuality, thus, they are not aware of the risks of acquiring genital infections such as STD’s, therefore they do not protect themselves through preservatives. These results show highly frequent STD’s, mostly the ones related to HPV, indicating the need for prevention measures, educational programs that aim at the reduction of this risk along with a specialized care by qualified professionals in order to make a correct diagnosis and, as a result, a treatment for the genital infections in the following up of the group.